Pinna nobilis refugia breached: Ongoing Mass Mortality Event in the Gulf of Kalloni (Aegean Sea) - NIKOLAOU, ATHANASIOS; PAPADIMITRIOU, EVANGELOS; KIOURANI, ELLI; KATSANEVAKIS, STELIOS (Mediterranean Marine Science, 2024)
The endemic Mediterranean fan mussel Pinna nobilis is on the brink of extinction due to an infectious disease that has caused an ongoing Mediterranean Mass Mortality Event (MME) since 2016. Currently, healthy P. nobilis populations can only be found in a few refuges, mainly transitional waters such as coastal lagoons and estuaries. In the eastern Mediterranean, the only remaining fan mussel population is located in the Gulf of Kalloni (Lesvos Island, Greece). This study reports on a severe mortality event that occurred during summer 2023, leaving the population decimated and limited mainly to young individuals. The estimated density of live individuals dropped from 1.22 to 0.23 individuals per 100 m², indicating an 81% population decline within approximately three months. The significant reduction in the P. nobilis population in the Gulf of Kalloni highlights the ongoing threat of MMEs. Continuous monitoring of P. nobilis and environmental variables, such as temperature and salinity, enhanced protection from anthropogenic pressures, and research into disease resistance mechanisms are crucial for the conservation of this critically endangered species.